Motor development in the hospitalized infant and its biological and environmental characteristics - Müller, Alessandra Bombarda; Pufal, Eunice Cristina; Bandeira, Paulo Felipe Ribeiro; Valentini, Nadia Cristina (Clinical and Biomedical Research, 2018)
Introduction: Hospitalization is a risk factor for delayed motor development, due to the lack of adequate stimulation; therefore, it is important to assess child development during hospital admission. Methods: In this study, motor development of previously healthy hospitalized infants was assessed and associated with biological and environmental characteristics, including length of hospital stay and physiotherapeutic treatment. The assessment was made before discharge, with questionnaires and a motor assessment scale. Results: The sample of 32 infants aged from zero to 18 months had an average length of hospital stay of 4.94 ± 2.39 days. 50% of infants were girls (n = 16) and mostly belonged to socioeconomic class C (n = 16). Length of hospital stay explained only 3.3% of motor development variation, showing no significant impact. Infants from lower socioeconomic classes were nearly six times more susceptible to motor delays than those belonging to higher classes (p = 0.05). During hospitalization, 25% of the sample (n = 8) was treated with physiotherapy. All these patients were hospitalized for respiratory dysfunction and presented five times less chance of altered motor development when compared to those who did not undergo physiotherapy. Conclusion: These results should be interpreted with caution, since the type of physiotherapy care provided and infant’s degree of motor impairment were unknown. In this study, length of stay and hospital environment were not significant risk factors when analyzed individually, concluding that the greater the exposure and the amount of associated factors, the more susceptible the infant will be to present motor delays. Keywords: Child development; hospitalization; developmental disabilities